2006
DOI: 10.1007/s00213-006-0340-4
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects of modafinil in marmoset monkeys

Abstract: Rationale: Modafinil is increasingly used in sleep disturbances in general and in neurodegenerative diseases and is recently being used in healthy people for attention control. However, the application of modafinil is possibly not only restricted to alertness enhancing effects. More insight in this compound may lead to new applications. Not all behavioral aspects have been studied sufficiently; therefore, more detailed investigations on modafinil's positive and aversive behavioral effects are addressed in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Indeed, we could find few references where i.p. modafinil produced hyperactivity in a novel environment, as opposed to dishabituation of activity in a familiar environment [33,42,40,43]. This is in sharp contrast to cocaine, which readily elicits locomotor activity even at very low doses in a novel environment [44].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we could find few references where i.p. modafinil produced hyperactivity in a novel environment, as opposed to dishabituation of activity in a familiar environment [33,42,40,43]. This is in sharp contrast to cocaine, which readily elicits locomotor activity even at very low doses in a novel environment [44].…”
Section: Discussionmentioning
confidence: 99%
“…This is an important issue of clinical relevance as other cognitive enhancers such as amphetamine have been shown to have a pronounced effect on emotional behavior, including the generation of fear and anxiety (Angrist and Gershon, 1970; Ellinwood et al , 1973; Hall et al , 1988) along with exaggerated amygdala reactivity during the perceptual processing of angry and fearful facial expressions (Hariri et al , 2002). Data from animal studies have shown either no effects of modafinil on anxiety scales (Hermant et al , 1991; Simon et al , 1994) or an anxiolytic effect (van Vliet et al , 2006). Results from studies conducted on humans are less consistent; some studies show either an anxiolytic effect (Becker et al , 2004), or no effect on anxiety ratings (Saletu et al , 2007; Samuels et al , 2006), while others report an anxiogenic effect (Broughton et al , 1997; MacDonald et al , 2002; Schwartz et al , 2003; Taneja et al , 2007; Zifko et al , 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is common for candidate pharmacotherapeutic drugs to induce hyperactivity or hypoactivity, presumably because these compounds engage and/or inhibit motor systems that functionally overlap with neural circuits that mediate motivated behavior (Bass et al 2002; Eaves et al 1985; Geter-Douglass et al 1997; Gyertyan and Saghy, 2004; Harrod et al 2001; Harrod et al 2003; Jarbe et al 2008; Le Foll et al 2008; Matsumoto et al 2008; Miller et al 2003; Simon et al 1995; van Vilet et al 2006; Vickers et al 2003). Such alterations in locomotor behavior are of interest to preclinical and clinical research because changes in locomotor activity may affect acceptability and compliance of a particular pharmacotherapy, and thus decrease the probability of successful treatment outcomes in individuals who exhibit SUD.…”
Section: Introductionmentioning
confidence: 99%